Rola pracy i nauczania w koncepcji wychowania integralnego Edmunda Bojanowskiego na tle europejskich prądów wychowawczych XIX wieku - Zjawin, Jacek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article shows the concept of integral education created by Blessed Edmund Bojanowski against the pedagogical views of his era. Ideas of organic work and work at the base, strong relationships of patriotism with Christian faith are just some of the inspirations for the education program still used today by the Sisters in their infant schools. Bojanowski, on the one hand, refers to the concept of great theoreticians of the 19th century education and, on the other, creates his own original pedagogical program, which instructs his sisters to apply in detail, thereby making his effectiveness dependent. This constant effectiveness can be an inspiration for solving contemporary problems of raising a young generation.